ナンキョク アスカ カンソク キョテン ニオケル ホウシャ カンソク ト タイキ・セツメン ノ ホウシャ トクセイ - 青木, 輝夫; アオキ, テルオ; Aoki , Teruo (1997)
P(論文) 南極あすか観測拠点(71°31′S, 24°08′E, 930m)における1988年の放射観測の概要を述べ, 放射収支観測の結果を他の基地における結果と比較しながら議論した。あすか観測拠点における雲による日々の正味放射の変動は, 短波が高々20W/m^2であるのに対し, 長波は40-60W/m^2と大きく, 全波長でも20-60W/m^2と長波が効いている。雲の効果は主に長波を通して放射収支に大きな影響を持っており, その大きさは季節変化の振幅や基地間の差に匹敵する。一方, 大気一積雪系の多重散乱モデルによって積雪面のアルベドのシュミレーションを行った。その結果積雪アルベドが積雪粒子の粒径, 太陽天頂角, 雲, 積雪構造によって変化することが再現された。また, 積雪物理量や雲と積雪の区別のリモートセンシングに近赤外域が有効であることが示された。 Radiation observations at Asuka Station (71°31′S, 24°08′E, 930m), Antarctica in 1988 are summarized and the radiation budget at Asuka is compared with those at other stations. The diurnal variations of net radiation due to cloud condition at Asuka are 20W/m^2 for shortwave, 40-60W/m^2 for longwave and 20-60W/m^2 for total radiation. Cloud have a large effect on the radiation budget mainly through longwave radiation. The magnitude of this effect is approximately equal to the amplitude of the seasonal variation and differences among the stations in Antarctica. On the other hand, snow albedo is simulated with a multiple scattering model for the atmosphere-snow system. The result is that the spectral albedo of snow depends on the snow grain size, solar zenith angle, cloud condition and structure of snow layers. It is shown that near infrared wavelengths are effective for remote sensing of the snow physical parameters and discrimination between the snow surface and clouds from space. departmental bulletin paper